2006
DOI: 10.1007/s11258-006-9193-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water level and temperature on performance of four Sphagnum mosses

Abstract: To evaluate the effects of changes in water level and temperatures on performance of four Sphagnum mosses, S. magellanicum, S. rubellum, S. imbricatum and S. fuscum were grown at two water levels, -5 cm and -15 cm, and at two temperatures, 15°C and 20°C. These species differ in their position along the microtopographical gradient and in their geographical distribution. Height increment, subcapitulum bulk density, biomass production, capitulum water content and cumulative evaporation were measured. Height incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 27 publications
4
103
3
3
Order By: Relevance
“…Other studies have shown that increased temperature can increase Sphagnum production (Asada et al 2003;Dorrepaal et al 2003;Gerdol 1995), but the temperatures used in those experiments were lower and varied between 8 and 15°C. Though Robroek et al (2007b) did find greater height increment and production at 20°C than at 15°C for several Sphagnum species, their experiment lasted for only 6 months. Harley et al (1989) and Skre and Oechel (1981) showed that photosynthesis in Sphagnum increases with temperature up to an optimum around 20-25°C.…”
Section: Temperaturementioning
confidence: 83%
See 1 more Smart Citation
“…Other studies have shown that increased temperature can increase Sphagnum production (Asada et al 2003;Dorrepaal et al 2003;Gerdol 1995), but the temperatures used in those experiments were lower and varied between 8 and 15°C. Though Robroek et al (2007b) did find greater height increment and production at 20°C than at 15°C for several Sphagnum species, their experiment lasted for only 6 months. Harley et al (1989) and Skre and Oechel (1981) showed that photosynthesis in Sphagnum increases with temperature up to an optimum around 20-25°C.…”
Section: Temperaturementioning
confidence: 83%
“…The composition of the vegetation also determines the characteristics of a peat bog. We have already found different responses in biomass production among species when temperature is increased (Breeuwer et al 2008a;Robroek et al 2007b). It seems likely that when a species with high production and/or a low decomposition rate increases its relative abundance in a bog, this will increase the carbon storage capacity of the system.…”
Section: Introductionmentioning
confidence: 92%
“…The higher temperatures elevate CO 2 respiration and may also stimulate plant productivity, especially in cold regions (Rustad et al 2001). Results of field experiments show the increased Sphagnum productivity with warming (Robroek et al 2007), as long as there was sufficient water (Dorrepaal et al 2003). In Linje mire, the noticeably lower Q10 values found in the dry treatment can be explained by changes in microclimate conditions that affect the microbial community (Luo et al 2001;Allison et al 2010;Crowther and Bradford 2013) and particularly by the lower peat moisture (Silvola et al 1996;Suseela et al 2012).…”
Section: Q10 Values Describe the Dynamics Of R Ecomentioning
confidence: 99%
“…Mean annual temperature together with PPFD during the growing season are the most important factors explaining Sphagnum productivity on the global scale (Gunnarsson, 2005;Loisel et al, 2012), and the temperature optimum of Sphagnum photosynthesis is known to change over the growing season (Gaberščik and Martinčič, 1987). However, the temperature dependence and acclimatization of species-level photosynthesis in peatlands has been studied only with a few Sphagnum species (Gaberščik and Martinčič, 1987;Robroek et al, 2007).…”
Section: Comparison Of Upscaled Gross Photosynthesis Values With Eddymentioning
confidence: 99%